Development and Validation of a Novel Tool for the Prediction of Clopidogrel Response in Chinese Acute Coronary Syndrome Patients: The GeneFA Score - Wu, Hongyi; Li, Xiaoye; Qian, Juying; Zhao, Xin; Yao, Yao; Lv, Qianzhou; Ge, Junbo (Frontiers in Pharmacology, 2022)
AIM: Growing evidence indicated that CYP2C19 genotypes could only explain a fraction of the pharmacodynamic response to clopidogrel, while a number of clinical factors also have contributing roles. Our objective was to develop a new risk score to improve prognostication of ischemic events in Chinese patients treated with clopidogrel. METHODS: A new risk score was developed and internally validated in 445 patients with acute coronary syndrome(ACS) undergoing coronary stenting. The final score was named GeneFA score based on inclusion of CYP2C19 genotype, fibrinogen, and age. External validation of the GeneFA score and comparison with the ABCD-GENE score were performed in an independent ACS cohort. RESULTS: Based on the observed frequencies of high platelet reactivity (HRPR) in relation to GeneFA risk score, a relative higher clinically HRPR was observed in upper quintile with representative score of 3 (52.90%) and 4 (59.10%), meanwhile it was found less frequently in the score 0 (6.70%),1 (15.10%) and 2 (16.70%) group. Participants with GeneFA score >2 had an increased risk of HRPR (54.3% vs. 14.7%, P< 0.001) and ischemic recurrence (20.7% vs. 5.4%, P<0.001). GeneFA score exhibited a better prediction for high HRPR patients as compared to ABCD-GENE score (P <0.001). In the validation population, GeneFA illustrated similarly high prognostic value for HRPR incidence (C-statistic: 0.709 for GeneFA and 0.683 for ABCD-GENE) and ischemic recurrence (C-statistic: 0.696 for GeneFA and 0.657 for ABCD-GENE) on clopidogrel, as compared to ABCD-GENE. CONSCLUSIONS: The GeneFA risk score had a moderate predictive ability for HRPR on clopidogrel for CAD patients in Chinese populations. The predictive value of GeneFA score was consistent with ABCD-GENE score for HRPR identification.